The Effectiveness of The use of Snake and Ladder Media in The Material of The Kingdoms of Islam, Hinduism and Buddhism Based on The Hots Problem of Students Learning Outcomes in Elementary Schools - Nuril Nuzulia (Universitas Muhammadiyah Sidoarjo, 2021)
This research is motivated by the availability of the snake and ladder game on the material of the kingdoms of Islam, Hinduism and Buddhism based on HOTS questions which have not been tested for their effectiveness on student learning outcomes. This study aims to reveal the effectiveness level of the use of snake and ladder media in the material of Islamic, Hindu and Buddhist kingdoms on student learning outcomes at SDN Ngaringan 03 Blitar. This type of research is a quasi-experimental research design with a non-equivalent control group design. The population in this study were grade 4 students at SDN Ngaringan Blitar. The research sample was taken using purposive sampling technique so that class 4A was selected as the experimental class and class 4 B as the control class. The instrument of this research is a test of learning outcomes by providing a pretest and posttest in the form of an objective test with 4 answer choices as many as 25 items taken from 40 questions that have been tested. The data analysis technique used was the N-Gain test and the two-mean similarity test (t-test). The results showed an increase in learning outcomes was better in the experimental class than in the control class. This is evidenced by the posttest mean scores of the experimental class and the control class respectively 92.12 and 73.96. This is also evidenced by the average N-Gain test for the experimental class of 0.762 with the high category and the control class of 0.294 in the low category, and supported by hypothesis testing carried out by t-test using the Independent Samples Test showing Sign 2 Tailed < 0.05, this indicates that the use of snake and ladder media is effective.